Structural Relationships among Environmental Engagement, Sustainable Behavior, and Happiness in University Students - Choi, Jihye (Opción, 2019)
The purpose of the study is to investigate the relationships among environmental engagement, sustainable behavior, and happiness. The study used structural equation modeling. It is to examine the relationship among these variables. We tested two structural equation models compared. The results revealed that the present data best fit Model 1. Environmental engagement has direct and indirect effects on happiness and is mediated by sustainable behavior (χ² (74) =151.094, TLI=.931 CFI=.944 RMSEA=.06). The results indicate that environmental engagement affects happiness. Also, environmental engagement affects happiness indirectly through the mediation of sustainable behavior. In closing, implications for environment education are discussed